The Foucauldian discourse on power in a woman's novel - Dy, Jerry (UP Los Baños Journal, 2009)
Text is indivisible from context. Literature is inseparable from history. A close reading of Rosca's State of War resonates Foucalt's poststrusturalist/postmodernist view of history as discourse on power. Two major forms of power relations recur in the novel's discursive formation: individualizing or pastoral and totalitarian or institutional. As a critique of Martial Law politics, the historical novel echoes strains of Foucault's Discipline and Punish, a sociological treatise on the modern penal system. Such a system situates the mode of discipline and punishment from the body to the soul. In privileging a strong female voice in the narrative, Rosca's novel appropriates counter-memory as the locus of the persona's resistance to state power. The result of such a rhetorical strategy is the (re)fashioning of an alternative history that fills in the gaps of a nation's fractured history.